A minimalist analysis of expletive daar (“there”) and dit (“it”) constructions in Afrikaans - De Bruin, Jeane (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA (General Linguistics))--University of Stellenbosch, 2011.